Sex Woman on Top, Sex Missionary, Sex Doggy Style and Sex 69 - Arsyad, Taufiq (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The sexual positions "sex woman on top, sex missionary, sex doggy style, and sex 69" have long been subjects of discussion in the context of human sexuality, yet a deep understanding of their psychological, social, and cultural implications remains limited. This research aims to explore the multidimensional impact of these sexual positions through a comprehensive qualitative literature review. Analysis of literature from various sources reveals four main themes: psychological and emotional impact, social and cultural perceptions, variations based on demographics, and implications for sexual satisfaction and relationship dynamics. Findings indicate that these positions can influence feelings of dominance, submission, and intimacy, with varying impacts depending on individual and relational contexts. Social and cultural perceptions of these positions are highly diverse, influenced by societal norms, media representation, and levels of sexual education. Demographic factors such as age, gender, and sexual orientation also affect attitudes and experiences related to these positions. The use of "sex woman on top, sex missionary, sex doggy style, and sex 69" can significantly impact sexual satisfaction and relationship dynamics, but their effectiveness depends on clear communication and consent between partners. This research highlights the importance of a holistic approach to understanding human sexual behavior and emphasizes the need for more comprehensive and inclusive sexual education. Implications for clinical practice and future research are also discussed.